Diagnostic Value of Plasmotec Malaria-3 Antigen Detection on Gold Standard Microscopy - Trieva Verawaty Butarbutar; Puspa Wardhani; Aryati Aryati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Plasmotec Malaria-3 is a rapid malaria diagnostic test that uses four-line tests and targets three malaria proteins, namely Plasmodium falciparum specific protein (HRP-2), Plasmodium vivax-specific LDH (Pv-LDH) and non-specific Plasmodium LDH (pLDH). Microscopy as a gold standard has many disadvantages and the availability of malaria Rapid Diagnostic Tests (RDTs) in detecting three proteins is still very limited. This study aimed to determine the diagnostic value of ® ® Plasmotec Malaria-3 against gold standard microscopy, comparing the Plasmotec Malaria-3 and microscopy antigen ® species detection, determining the Parasitemia Index (PI) cut-off using Plasmotec Malaria-3. This study was a cross-sectional study with 105 whole blood samples obtained from the Merauke Papua General Hospital which fulfilled the inclusion and exclusion criteria. Samples were examined by thick and thin drops and then examined with Plasmotec® ® Malaria-3. Diagnostic values of Plasmotec Malaria-3 against the microscopy were Sn 100%, Sp 98.04%, PPV 98.18%, NPV ® 100%, LR + 51, LR-0, diagnostic accuracy of 99.05%. Comparison of Plasmodium species between Plasmotec Malaria-3 and ® microscopy was not significantly different, p-value = 0.172. The cut-off of PI in P.falciparum and P.vivax in Plasmotec Malaria-3 based on the Receiver Operating Characteristic (ROC) curve could not be determined with AUC=0.577, p-value=0.385 and AUC=0.423, p-value=0.385, respectively. This study concluded that the comparison of Plasmodium ® species between Plasmotec Malaria-3, and microscopy was not significantly different. This study suggested that further ® research is needed to find the diagnostic value of non-falciparum and non-vivax Plasmodium against Plasmotec Malaria-3.